Efektifitas Manajemen Sarana Prasarana dan Tata Laksana Pendidikan Islam di Sekolah Tinggi Agama Islam Rahmaniyah Sekayu - Zulkipli Zulkipli (El-Idare, 2020)
This article aimed to determine the effectivity level of infrastructure management and governance of Islamic education at Islamic High School Rahmaniyah Sekayu. The approach was mix method namely by combining quantitative and qualitative methods. Research information sourced by school-chairman, vice-chairman I, II and III, heads of BAU and BAK and 100 university students. Data collection methods were obtained from observation, documentation, interviews and questionnaires. Data analysis techniques used quantitative data analysis which reinforced by qualitative data analysis. Study result showed that the effectivity level of the management of Islamic education at Islamic High School Rahmaniyah Sekayu in terms of infrastructure management was included in high category (80,08%) and governance management was included in sufficient category (74,13%).